Enabling 'growth mindsets' in engineering students - Campbell, Anita (University of Cape Town, 2020)
Student failure is often attributed to a lack of work by students. While this view has some merit, it implies that only students need to change and reduces the incentive for lecturers, curricula, assessment practices to be interrogated. In this thesis, I take a comprehensive look into why students do not work. Firstly, I place social psychology factors in context with other factors that impact student success and show how beliefs about academic ability underpin the academic behaviour that leads to success. By placing a learning theory lens on six characteristics of fixed mindsets (beliefs that ability can only be developed to an individually pre-determined level) and growth mindsets (beliefs that that effective effort will lead to unlimited self-improvement), I develop a theoretical framework that explains how both fixed and growth mindsets can be encouraged by teaching practices. As students with fixed mindsets may be more vulnerable to dropping out of university, lecturers should be aware of the mindset messages they are sending to students through their words, actions and choice of activities and assessment practices. To address the question of how growth mindsets can be developed, I present results from a systematic literature review of growth mindset interventions aimed at engineering students, drawing on databases in education, engineering, and psychology. The findings show that most interventions involved informing students about mindsets and asking students to reflect on or teach others about mindsets, using personal examples. An intervention was devised to develop growth mindsets in engineering students through tutoring groups on the social media platform WhatsApp. Poor group functioning was addressed using a design-based research approach for the establishment of effective groups. Unexpectedly, assessments of engineering students' mindsets through surveys and interviews showed very low numbers of students with fixed mindset views. Reasons for this result are explained by categorizing growth mindset enablers identified from literature and comparing the literature findings with interview data from engineering students. The thesis culminates by contributing a critique on mindset assessment and a framework for creating learning environments conducive to student success.